2010
DOI: 10.1007/s12033-010-9336-8
|View full text |Cite
|
Sign up to set email alerts
|

Human Protein Reference Database and Human Proteinpedia as Discovery Resources for Molecular Biotechnology

Abstract: In the recent years, research in molecular biotechnology has transformed from being small scale studies targeted at a single or a small set of molecule(s) into a combination of high throughput discovery platforms and extensive validations. Such a discovery platform provided an unbiased approach which resulted in the identification of several novel genetic and protein biomarkers. High throughput nature of these investigations coupled with higher sensitivity and specificity of Next Generation technologies provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 109 publications
0
56
0
Order By: Relevance
“…The classifications were based on annotations in HPRD. 16,17 Our analysis revealed that 21% of the proteins were involved in regulation of nucleic acid metabolism; 18% in signal transduction, 15% in cell communication and 11% in cellular growth and maintenance. Classification of the proteins based on subcellular localization revealed 40% of the hyperphosphorylated proteins localized to the nucleus and 25% localized to the cytoplasm.…”
Section: Identification Of Dysregulated Phosphoproteins In Hnscc Cellmentioning
confidence: 92%
See 1 more Smart Citation
“…The classifications were based on annotations in HPRD. 16,17 Our analysis revealed that 21% of the proteins were involved in regulation of nucleic acid metabolism; 18% in signal transduction, 15% in cell communication and 11% in cellular growth and maintenance. Classification of the proteins based on subcellular localization revealed 40% of the hyperphosphorylated proteins localized to the nucleus and 25% localized to the cytoplasm.…”
Section: Identification Of Dysregulated Phosphoproteins In Hnscc Cellmentioning
confidence: 92%
“…16,50 Pathway analysis was done using GeneSpring GX software (version 12.6.1). Using Pathway Architect module of GeneSpring GX, the proteins that were found to be overexpressed and hyperphosphorylated in at least four cell lines with a fold change of 1.5 was included for pathway analysis.…”
Section: Bioinformatics Analysismentioning
confidence: 99%
“…The newest versions of human protein-protein interaction dataset were available from HPRD, BioGRID and IntAct, respectively (Goel et al, 2011;Kerrien et al, 2012;Chatr-Aryamontri et al, 2013). These interactions are derived from literatures of experimentally validation and reliable for widely application in disease researches combined with human PPI network.…”
Section: Ppi Sub-network Constructionmentioning
confidence: 99%
“…Interacting proteins have been observed to have topologically similar phylogenetic trees for the corresponding protein families, presumably due to the co-evolution of cooperating proteins (Fryxell, 1996;Goh et al, 2000;Pages et al, 1997). Based on the above observation, the phylogenetic similarity method was proposed.…”
Section: Phylogenetic Relationshipmentioning
confidence: 99%